Sistem Administrasi Akademik Sekolah Dasar Islam Terpadu Asa Sumbawa Berbasis Web Untuk Pelayanan Terintegrasi - Muhammad Faqih Al Faruq; Esabella, Shinta; Idifitriani, Farida (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The Integrated Islamic Elementary School Asa Sumbawa is an educational institution that implements two curricula, namely the Integrated Islamic School Network (JSIT) and the Independent Curriculum in Sumbawa Regency. The empowerment of technology in the academic administration of the Integrated Islamic Elementary School Asa Sumbawa is still done manually. This research aims to design a Web-Based Academic Administration System for the Integrated Islamic Elementary School Asa Sumbawa: For Integrated Services, which aims to produce a digital product in the form of a web-based system with an attractive interface and various supporting features, including an academic information menu, user management menu, payment billing menu, lesson schedule menu, class menu, and grades menu. This research uses qualitative methods with three data collection methods: observation, interviews, and document studies. The system is designed using the waterfall development methodology, with unified modeling language modeling, Laravel framework, and PHP programming language, as well as black box testing for system testing. It is hoped that the presence of this system can help make the academic administration process of the Integrated Islamic Elementary School Asa Sumbawa more effective and efficient.